2018
DOI: 10.3329/bjas.v46i3.36316
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Nageswari duck of Bangladesh under intensive management condition

Abstract: The present study was conducted to know the production and reproduction potentials, and egg quality characteristics of Nageswari duck under intensive management condition. Data were collected from a nucleus flock of Nageswari ducks that have been maintained from day old to 72 weeks of age at AI center, Bangladesh Agricultural University, Mymensingh, from May 2015 to October 2016. Irrespective of sex, the average live weight of ducklings at day old, 1st, 3rd, 5th, 7thand 9thweeks of age were observed to be 38.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…);Vij et al (2010) in West Bengal duck,Kamal et al (2020) in Maithili duck Tai et al (1989). reported lower than the present body weight in Brown Tsaiya duck Bhuiyan et al (2017). reported 1401 g weight at sexual maturity in Nageswari duck of Bangladesh which was lower than the present study.…”
contrasting
confidence: 64%
“…);Vij et al (2010) in West Bengal duck,Kamal et al (2020) in Maithili duck Tai et al (1989). reported lower than the present body weight in Brown Tsaiya duck Bhuiyan et al (2017). reported 1401 g weight at sexual maturity in Nageswari duck of Bangladesh which was lower than the present study.…”
contrasting
confidence: 64%
“…Sharma et al (2002) reported that the eggs of Nageswari ducks of Assam are large sized (62.45 g), thick shelled and of good quality with appealing greenish blue colour. In Bangladesh, the 9 th week body weight, the age at first egg production, hen day egg production and annual egg production per duck of Nageswari ducks were 1076.11 g, 130 days, 55.67% and 204.23, respectively (Bhuiyan et al 2017).…”
Section: Important Duck Breedsmentioning
confidence: 98%
“…Nageswari (N) is an egg type indigenous duck breed of Bangladesh having black or penciled black plumage color except white in breast region. Under intensive management condition, the average annual egg production was 204.23±14.19 and the 9 th week live weight was only 1076.11±16.34 g Morphology, Morphometry, Growth Performance and Carcass Characteristics of Pekin, Nageswari and Their F 1 Crossbred Ducks under Intensive Management (Bhuiyan et al, 2017). However, this breed is well adapted to agro-climatic condition and existing management system of Bangladesh (Morduzzaman et al 2015).…”
Section: Introductionmentioning
confidence: 97%